Imagens e textos de africanos e afro-brasileiros : análise de livro didático de História em Mato Grosso - Moreira, Adriana Palhana (2020)
The present Master's research, developed in the line of research ―Historical Knowledge in Different Spaces of Memory‖ in ProfHistória of the Federal University of Mato Grosso aims to analyze the presentation of Africans and Afro-Brazilians in the didactic collection of History, Society and Citizenship Alfredo Boulos Junior (PNLD 2017/2018/2019) dialoguing through the approach of texts and images. As a theoretical basis, we used the authors Circe Bittencourt, who discusses History Teaching and its methodologies, and Kazumi Munakata and Choppin, who bring us a discussion about the Didactic Book (LD). We present Law 10.639 / 03 which deals with the obligation to teach Afro-Brazilian and African History and Culture in schools, as amended by Law 11.645 / 08 which makes the study of Afro-Brazilian and Indigenous History and Culture mandatory to contextualize the need for discussion about Africans and AfroBrazilians. Methodologically, the texts and images of the 7th and 8th year volumes are covered in the History, Society and Citizenship Collection of Alfredo Boulos Júnior (PNLD 2017/2018/2019) with a focus on the way Africans and Afro-Brazilians are approached in the pages of the book didactic. Questioning the conceptions of Culture, memory, work and dialoguing about the possibilities of overcoming stereotypes related to Afro-Brazilians and how they are presented in the textbook for students. Starting from the perspective of Historical Education, we propose the elaboration of classesworkshops. Theoretically we are based on the studies of Isabel Barca, who says that Historical Education is born from the concern with meaningful learning, in concrete contexts, linking theory and practice. Thus, the proposed classes-workshops contain images and texts that deal with African and Afro-Brazilian history and culture with approaches that contribute to the (re) writing of the history of these subjects, in order to contribute to the teaching of history.